Money Disorders and Locus of Control: Implications for Assessment and Treatment - Colby D. Taylor; Bradley Klontz; Derek Lawson (Journal of Financial Therapy, 2017)
Research has implicated locus of control (LOC) as a factor in the development of psychological disorders, but few studies have examined how LOC relates to money disorders, which occur when stress surrounding money negatively impacts financial health. The present study utilized hierarchical regression to examine how select demographic factors and LOC contribute to 7 distinct money disorders among a sample of 164 college students. Results demonstrate that the link between external LOC and money disorders is stronger than indicated by previous research. Unlike demographic factors, which are static and were not found to predict money disorders in the present study, LOC is amenable to change, and both financial planners and mental health professionals may wish to incorporate locus of control into assessment and intervention.
Keywords: locus of control; money disorders; disordered money behaviors; compulsive buying disorder; hoarding disorder; gambling disorder; financial enabling; financial dependence; workaholism